Pengaruh Teknik Cognitive Restructuring Terhadap Body Image Siswa Kelas XI IPA di MA Assaâ€™adah Labuapi Tahun Pelajaran 2024/2025 - Dewi, Sulistia; Sarilah, Sarilah (Transformasi : Jurnal Penelitian dan Pengembangan Pendidikan Non Formal Informal, 2025)
Abstract: Body image is a person's perception or assessment of their body. Adolescence is the age at which a person experiences various changes such as emotional, cognitive, social, and physical changes that lead to feelings of inadequacy or dissatisfaction with their physical appearance in an effort to meet existing beauty standards. In addition, there are many terms or phenomena among adolescents that suggest being beautiful or handsome is believed to be one of the advantages that facilitate daily activities. Based on this issue, an alternative solution is implemented, which is to use the cognitive restructuring technique. The formulation of the problem in this study is whether there is an influence of cognitive restructuring techniques on the body image of class XI science students at MA Assaâ€™adah Labuapi in the 2024/2025 academic year. The goal of this research is to determine the effect of the Cognitive Restructuring technique on the body image of 11th-grade science students at MA Assa'adah Labuapi for the 2024/2025 academic year. The data collection technique used is the distribution of questionnaires as the main method, with observation, interviews, and documentation as supplementary methods. The data analysis technique used in this research employs the t-test formula, with the calculations showing a t-calculation value of 20 and a t-table value at a 5% significance level with d.b (N-1) = 4 of 2.776. Thus, the t-calculation value is greater than the t-table value (20 > 2.776). Therefore, it can be concluded that there is an effect of the Cognitive Restructuring Technique on the body image of 11th-grade science students at MA Assa'adah Labuapi for the 2024/2025 academic year, making the results of this study stated as "Significantâ€.Key Words:Â Cognitive Restructuring, Body ImageAbstrak: Body image merupakan persepsi atau penilaian seseorang terhadap tubuhnya. Usia remaja seseorang yang di mana mengalami berbagai perubahan seperti emosional, kognitif, sosial dan perubahan fisik yang di mana timbulnya rasa kurang atau merasa tidak puas terhadap fisik yang dimiliki seseorang untuk berusaha untuk mengikuti standar kecantikan yang ada. Selain itu banyaknya istilah atau fenomena di kalangan remaja yang di mana menjadi cantik dan ganteng yang di percaya merupakan salah satu keberuntungan dalam mempermudah kegiatan sehari-hari. Berdasarkan masalah tersebut, maka alternatif solusi yang di lakukan yaitu dengan menggunakan Teknik cognitive restructuring Rumusan masalah dalam penelitian ini adalah apakah ada pengaruh teknik cognitive restructuring terhadap body image siswa kelas XI IPA di MA Assaâ€™adah Labuapi Tahun Pelajaran 2024/2025? Tujuan yang ingin dicapai dalam penelitian ini adalah untuk mengetahui pengaruh teknik Cognitive Restructuring terhadap body image siswa Kelas XI IPA di MA Assaâ€™adah Labuapi Tahun Pelajaran 2024/2025?. Teknik pengumpulan data yang digunakan adalah pemberian angket sebagai metode pokok dan metode observasi, wawancara dan dokumentasi sebagai metode pelengkap. Teknik analisis data yang digunakan dalam penelitian ini menggunakan rumus t-tes dengan hasil perhitungan yang menunjukkan nilai t-hitung sebesar 20 dan nilai t-tabel dengan taraf signifikansi 5% dengan d. b (N-1) = 4 sebesar 2,776. Dengan demikian nilai t-hitung lebih besar dari pada nilai t-tabel (20>2,776). Sehingga dapat disimpulkan bahwa ada pengaruh Teknik Cognitive Restructuring Terhadap Body Image Siswa kelas XI IPA di MA Assaâ€™adah Labuapi Tahun Pelajaran 2024/20.Kata Kunci:Â Cognitive Restructuring, Body Image